PELAKSANAAN PENGAWASAN KAWASAN MINAPOLITAN DI KECAMATAN XIII KOTO KAMPAR KABUPATEN KAMPAR - FAJRI HS, VERA WATI; Yuliani, Febri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Riau Province is an area that very much has the potential if developedand managed as well as possible then it will be able to increase revenue ( PAD ),particularly in District XIII Koto Kampar Kampar Regency in Minapolitandevelopment. Minapolitan supervision in District XIII Koto Kampar Kampardistrict conducted by the relevant agencies and consortia minapolitan fisheriesdepartment and the evaluation made by the minister of fisheries and marinerepublic of Indonesia every year. With the need for an evaluation of thedevelopment of the Minapolitan then to implement the control program planningin this area Minapolitan for achieving those objectives. But in fact in theimplementation and the work that is not fit for purpose and not runningoptimally so that the process of achieving goals is not running optimally.The aim of this study to see how the implementation of surveillanceMinapolitan in District XIII Koto Kampar Kampar regency and the factors thataffect the implementation of the surveillance. Theoretical concept that is in useis the theory of control, the indicators in this study exspectation, allocation,performance monitoring and correction action.From the results, it can be concluded that the control, or supervision isvery important that the role of the personal who already has the job, and run thesupervisory authority in this case is the Working Group and the Kampar DistrictXIII Koto Kampar District Fisheries Department needs to increase oversightMinapolitan where indigenous factors customs and participation of thecommunity is affected Minapolitan Region Implementation Oversight in DistrictXIII Koto Kampar Kampar regency.Keywords : Minapolitan , region , supervision